Melatonin reduces cholesterol accumulation and prooxidant state induced by high cholesterol diet in the plasma, the liver and probably in the aorta of C57BL/6J mice - (:unkn) unknown (WILEY, 2004)
We examined the hypolipidemic and antioxidative effects of melatonin in plasma, liver and aorta of C57BL/6J mice fed on a high cholesterol (HC) diet. Mice were fed normal mice chow containing 1.5% cholesterol and 0.5% cholic acid for 4 months with or without melatonin (10 mg/L in drinking water) treatment. HC diet was observed to increase cholesterol, triglyceride and diene conjugate (DC) levels in plasma and liver. There was a tendency towards an increase in cholesterol level in the aorta following HC diet. In addition, aortic DC levels were higher than those of control group. No fatty streaks or plaques developed in the aorta of mice following HC diet, but in some sections, derangement of the endothelial layer was detected. Melatonin treatment was found to reduce plasma, liver cholesterol and DC levels as well as liver triglyceride levels in hypercholesterolemic mice. Aortic cholesterol and DC levels were also reduced in hypercholesterolemic mice when given melatonin, although not statistically significant. There were no differences in aortic histopathological findings of mice fed on a HC diet with and without melatonin treatment. In conclusion, our results indicate that melatonin reduces HC diet-induced cholesterol accumulation and prooxidant state in the plasma, liver and probably in the aorta.
Keywords: atherosclerosis; C57BL/6J mice; high cholesterol diet; lipid peroxidation; melatonin; LIPID-PEROXIDATION; SERUM-CHOLESTEROL; OXIDATIVE DAMAGE; INJURY; RATS; SUPPLEMENTATION; GLUTATHIONE; ISCHEMIA; RABBITS; OIL